Quality of life questionnaire for women with gestational diabetes mellitus (GDMQ-36): development and psychometric properties - S. Mokhlesi; M. Simbar; F. Ramezani Tehrani; N. Kariman; H. Alavi Majd (BMC, 2019)
Abstract Background Gestational diabetes mellitus carries serious risks to mother and fetus and causes social, mental, and psychological consequences which can affect mothers' quality of life. Accordingly, this study aims to develop and assess the psychometric properties of quality of life questionnaire for women with gestational diabetes mellitus. Methods A methodological study of sequential exploratory mixed method was developed and implemented. It included qualitative (development of a quality of life questionnaire for mothers with GDM) and quantitative (assessment of psychometric prosperities of quality of life questionnaire for mothers with GDM) phases. Results Based on the findings of the qualitative phase and literature review, the primary questionnaire was prepared with 142 items. The outcome of face validity and content validity assessment was a 67-item questionnaire. S-CVI and S-CVR turned out to be 0.92 and 0.68, respectively. The results of exploratory factor analysis yielded an instrument with 36 items in five domains including concerns about high-risk pregnancy, perceived constraints, disease complications, medication and treatment, and support. Five factors explained 46.68% of the total variance of the questionnaire. The results indicated a moderate and significant correlation between the questionnaire of "Diabetes Clients Quality Of Life" and the researcher-made questionnaire (r = 0.63). Cronbach's alpha coefficient for the entire scale was 0.93 and the intra-class correlation coefficient was 0.95. Conclusion Quality of life questionnaire for mothers with GDM is a valid and reliable tool capable of measuring the quality of life of women with GDM.